Maternal depression and inflammation during pregnancy. Issue 11 (23rd August 2020) - Lahti-Pulkkinen, Marius; Girchenko, Polina; Robinson, Rachel; Lehto, Soili M.; Toffol, Elena; Heinonen, Kati; Reynolds, Rebecca M.; Kajantie, Eero; Laivuori, Hannele; Villa, Pia M.; Hämäläinen, Esa; Lahti, Jari; et al.
Abstract : Background: Maternal depression during pregnancy increases the risk for adverse developmental outcomes in children. However, the underpinning biological mechanisms remain unknown. We tested whether depression was associated with levels of and change in the inflammatory state during pregnancy, if early pregnancy overweight/obesity or diabetes/hypertensive pregnancy disorders accounted for/mediated these effects, and if depression added to the inflammation that typically accompanies these conditions. Methods: We analyzed plasma high-sensitivity C-reactive protein (hsCRP) and glycoprotein acetyls at three consecutive stages during pregnancy, derived history of depression diagnoses before pregnancy from Care Register for Healthcare (HILMO) ( N = 375) and self-reports ( N = 347) and depressive symptoms during pregnancy using the Center for Epidemiological Studies Depression Scale completed concurrently to blood samplings ( N = 295). Data on early pregnancy body mass index (BMI) and diabetes/hypertensive pregnancy disorders came from medical records. Results: Higher overall hsCRP levels, but not change, during pregnancy were predicted by history of depression diagnosis before pregnancy [HILMO: mean difference (MD) = 0.69 standard deviation (s.d. ) units; 95% confidence interval (CI) 0.26–1.11, self-report: MD = 0.56 s.d. ; 95% CI 0.17–0.94] and higher depressive symptoms during pregnancy (0.06 s.d. per s.d. increase; 95% CI 0.00–0.13). History of depression diagnosis before pregnancy also predicted higher overall glycoprotein acetyls (HILMO: MD = 0.52 s.d. ; 95% CI 0.12–0.93). These associations were not explained by diabetes/hypertensive disorders, but were accounted for and mediated by early pregnancy BMI. Furthermore, in obese women, overall hsCRP levels increased as depressive symptoms during pregnancy increased ( p = 0.006 for interaction). Conclusions: Depression is associated with a proinflammatory state during pregnancy. These associations are mediated by early pregnancy BMI, and depressive symptoms during pregnancy aggravate the inflammation related to obesity.